(untitled) (Global Journal of Science Frontier Research, 2014)
We examined fishery as a supplementary source of protein for bridging the gaps created by the birds ’saga in meeting the need for protein in less developed countries. A one step algorithm is proposed, implemented on von Bertalanffy and on seasonal growth models for the evaluation of the desired enhancement in fish growth. Precautionary measure is presented against the use of poultry wastes as a component commonly used in the formulation of fishery feeds. The one-step method gives an enhanced projection in fish growth and also predicts the appropriate proportion of all other constant parameters that will be needed.